Analysis of Dimensions of Prosocial Behavior in an Argentinean Sample of Children - Richaud, Maria Cristina (2012)
The aim is to determine how many factors or dimensions could explain the prosocial behavior, from the point of view of motivation. A sample of 472 middle class children and adolescents, both sexes, from Buenos Aires, Argentina completed the Spanish version of Prosocial Tendencies Measure (Carlo & Randall, 2002). The results of both exploratory and confirmatory factor analyses suggest that a four-factor structure seems more appropriate to explain the motivations for carry out a prosocial behaviour than one of six factors, as proposed by Carlo and Randall (2002). Finally the correlations between the four dimensions found in this article reinforce the hypothesis that the only prosocial behaviour selflessly motivated is altruism.